Burnout and Psychological Wellbeing Among Psychotherapists: A Systematic Review - Van Hoy, Angelika; Rzeszutek, Marcin (Frontiers in Psychology, 2022)
Objectives. The general aim of this systematic review is to synthesize, analyze, and critically review existing studies concerning the relationship between sociodemographic, intrapersonal, and work-related factors and burnout, as well as psychological well-being among psychotherapists. Methodology. We performed a structured literature search utilizing the PRISMA framework in the following databases: Web of Science, Scopus, MedLine, PsyARTICLES, ProQuest, and Google Scholar. The most relevant inclusion criteria were quantitative and peer-reviewed articles published in English. Results. After the selection process, we accepted 52 articles for further systematic review. Thirty-eight studies examined burnout among psychotherapists, while the other 14 studies focused on psychological well-being in this sample. Conclusions. Burnout and well-being among psychotherapists are related to numerous sociodemographic (e.g., age, gender), intrapersonal (e.g., coping, personality), and work-related characteristics, including work settings and professional support in this profession (e.g., supervision or personal therapy). However, the high heterogeneity observed between studies in terms of burnout and well-being operationalization and measurement warrants more consistent and advanced methodological models of these theoretical constructs in the future in this specific sample.